A comparison on shear performance of pad foundation using BS8110, EC2 and ACI318 - Mohammad, Panjehpour; Victor, Kumala Putra (INTI International University, 2018)
This research aims to compare the design and analysis outcomes of British Code (BS 8110), Eurocode (EC2) and American code (ACI 318) on pad foundation by utilising Autodesk Robot 2018 and Excel spreadsheets. It sheds some lights on the differences among the three aforementioned codes regarding punching shear stress of pad foundation. The shear performance, particularly the punching shear, are scrutinised by taking the axial load and biaxial moments into account. The key variables are size of pad foundation. The research reveals that ACI-318 design provides the lowest overall shear stress followed by EC2 design and then BS8110 design. Nevertheless, EC2 design provides the lowest punching shear stress followed by BS8110 design and then ACI-318 design. The punching shear stress in critical perimeter is primarily governed by length and width of foundation followed by concrete cover and length of column. This research is confined to shear design and shear analysis of reinforced concrete pad foundation with the primary focus on punching shear stress. The research also touches upon the required shear reinforcements recommended by the three codes. The scope of this research is confined to only short columns.